Hands-on Projects: a Technique for Improving Studentsâ Involvement of Speaking Class - *, Ratnawati (Proceeding of International Conference on Teacher Training and Education, 2016)
Demotivated and insecure students in speaking class were found at second grade students of Galuh University, Ciamis, West Java. The observed problems came from the studentsâ involvement was poor in whole classroom activities especially speaking class. Hence, this study would like to improve it through hands-on project during a semester. This study employed descriptive qualitative with some included steps planning, acting, reflecting, and observing. Observation and questionnaire were administered to collect information from students. From the result of observation and questionnaire, they were found that applying hands-on project for speaking class got positive result. Moreover, studentsâ involvement grew significantly during classroom activities. In line with findings, it can be said that this technique has got significant effects toward studentsâ involvement in speaking class. So, educators need to apply it as their choices in future planning lesson.